Electric field switching between blue-green and red cathodoluminescence in poly(4,4 '-diphenylene diphenylvinylene) mixed with ZnO : Mg nanoparticles - Panin, GN; Kang, TW; Aleshin, AN; Baranov, AN; Oh, YJ; Khotina, IA (AMER INST PHYSICS, 2005)
We report the effect of reversible switching between blue-green and red cathodoluminescence (CL) in poly(4,4(')-diphenylene diphenylvinylene) (PDPV), mixed with the 12-60 nm size ZnO:Mg nanoparticles by applying an electric field. We found that without electric field the CL emission maximum is in the blue-green region for a PDPV-ZnO:Mg composite deposited on Si-SiO2 substrate with gold electrodes. Application of positive bias suppressed the blue-green emission and shifted the emission maximum to the red region. The mechanism for the formation of the exited states in PDPV-ZnO:Mg structure implies the presence of radiative recombination channels, which can be controlled by an electric field. (C) 2005 American Institute of Physics.